MITF and TFEB cross-regulation in melanoma cells - Ballesteros-Álvarez, Josué; Dilshat, Ramile; Fock, Valerie; Möller, Katrín; Karl, Ludwig; Larue, Lionel; Ögmundsdóttir, Margrét Helga; Steingrímsson, Eiríkur (PLOS ONE, 2020)
The MITF, TFEB, TFE3 and TFEC (MiT-TFE) proteins belong to the basic helix-loop-helix family of leucine zipper transcription factors. MITF is crucial for melanocyte development and differentiation, and has been termed a lineage-specific oncogene in melanoma. The three related proteins MITF, TFEB and TFE3 have been shown to be involved in the biogenesis and function of lysosomes and autophagosomes, regulating cellular clearance pathways. Here we investigated the cross-regulatory relationship of MITF and TFEB in melanoma cells. Like MITF, the TFEB and TFE3 genes are expressed in melanoma cells as well as in melanoma tumors, albeit at lower levels. We show that the MITF and TFEB proteins, but not TFE3, directly affect each other’s mRNA and protein expression. In addition, the subcellular localization of MITF and TFEB is subject to regulation by the mTOR signaling pathway, which impacts their cross-regulatory relationship at the transcriptional level. Our work shows that the relationship between MITF and TFEB is multifaceted and that the cross-regulatory interactions of these factors need to be taken into account when considering pathways regulated by these proteins.